DETERMINANTS OF HEALTH SERVICE UTILIZATION AMONG PAKISTANI IMMIGRANTS IN MARYLAND, USA - Khan, Shahzad Ali; Manzoor, Khola (Journal of Ayub Medical College Abbottabad, 2014)
Background: Health of immigrants is challenge for any host country due to multiple reasons. Immigrants of Pakistani origin constitute a significant population in the USA and their population has doubled in last 10 years. This study was conducted to determine factors affecting health service utilization in the state of Maryland, USA. Methods: This was a descriptive study, utilizing mixed method research. A sample of 100 respondents from Pakistani immigrants in Maryland was selected through convenience sampling. A structured questionnaire was used for soliciting responses. Three focus group discussions were also conducted for qualitative assessment of health service utilization. Results: Male gender, higher level of education, longer duration of stay, and higher income people had more utilization of health services. Those not having insurance had affordability issues as they had to pay out of pocket for treatment cost. A high proportion of uninsured were resorting to traditional home remedies for treatment. There was a concern on delays in appointment system and long waiting time for elective cases. Most respondents mentioned problem of language while interacting with doctors and need of English speaking family member in medical consultation. Many respondents reported difficulty in availing health services due to job commitments. They had to make arrangements for substitute at their workplaces, which affected their utilization of health services. Conclusion: Low-income immigrants in USA are less likely to have health insurance. Factors affecting service use are out of pocket costs, long waiting time, language problems and immigrants' job commitments. It is recommended to get a clear idea of health systems of USA before moving to US as immigrant. Keywords: immigrant, insurance, health services utilization